2017
DOI: 10.1038/ajg.2017.208
|View full text |Cite|
|
Sign up to set email alerts
|

Rural and Urban Residence During Early Life is Associated with Risk of Inflammatory Bowel Disease: A Population-Based Inception and Birth Cohort Study

Abstract: Objectives:To determine the association between inflammatory bowel disease (IBD) and rural/urban household at the time of diagnosis, or within the first 5 years (y) of life.Methods:Population-based cohorts of residents of four Canadian provinces were created using health administrative data. Rural/urban status was derived from postal codes based on population density and distance to metropolitan areas. Validated algorithms identified all incident IBD cases from administrative data (Alberta: 1999–2008, Manitoba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(61 citation statements)
references
References 24 publications
2
59
0
Order By: Relevance
“…There may also be a truly increased incidence of IBD among younger individuals resulting from increasing urbanization and household changes in South Korea. Previous studies have shown that residing in an urban setting is associated with higher incidences of both CD and UC whereas residing in rural areas provides a protective effect that was prominent among younger (< 30 years) age groups . South Korea has experienced rapid urbanization, a significant increase in the number of young, urban singles, and a concomitant increase in the number of lone dwellers aged < 30 years .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There may also be a truly increased incidence of IBD among younger individuals resulting from increasing urbanization and household changes in South Korea. Previous studies have shown that residing in an urban setting is associated with higher incidences of both CD and UC whereas residing in rural areas provides a protective effect that was prominent among younger (< 30 years) age groups . South Korea has experienced rapid urbanization, a significant increase in the number of young, urban singles, and a concomitant increase in the number of lone dwellers aged < 30 years .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that residing in an urban setting is associated with higher incidences of both CD and UC whereas residing in rural areas provides a protective effect that was prominent among younger (< 30 years) age groups. 25,26 South Korea has experienced rapid urbanization, a significant increase in the number of young, urban singles, and a concomitant increase in the number of lone dwellers aged < 30 years. 27 In addition, fresh food and vegetable consumption remains low, and dining out has grown substantially, especially among young singles (KOSIS, http://kosis.kr/).…”
Section: Epidemiology Of Ibd In Koreamentioning
confidence: 99%
“…We highlight two recent multi-province studies conducted by the Canadian Gastro-Intestinal Epidemiology Consortium that evaluated rural-urban differences in the epidemiology of IBD (Benchimol et al 2017) and health services utilization and outcomes in patients with IBD (Benchimol et al 2018).…”
Section: The Issuementioning
confidence: 99%
“…While neighbourhood deprivation has been linked to health and disease,5 data on IBD are scarce 6. In this nationwide study of more than 4 million Swedish residents, some 20 000 individuals developed IBD after the age of 10 years.…”
mentioning
confidence: 90%